ANALISIS DAMPAK ZAKAT TERHADAP KESEJAHTERAAN MUSTAHIK - Purnama, Andika; Hafidhudin, Didin; Ayuniyyah, Qurroh (Kasaba, 2024)
In an effort to alleviate poverty and improve the welfare of the people, one of the instruments used in Islamic economics is zakat. The potential for zakat in Indonesia is very large. In In 2020, Indonesia's zakat potential is worth IDR 327.6 trillion. Zakat instrument is expected to be part of the solution to improve the welfare of mustahik. However, the effectiveness and efficiency of the programs held by the Amil Zakat Agency and institutions cannot be measured. The purpose of the study was to determine whether or not there is an impact of zakat in form the welfare of mustahik. This research was conducted in a case study of zakat management at BAZNAS Pangkalpinang City with a sample of 50 mustahik. Techniques/methods of analysis and data processing in the form of a quantitative approach, field studies by filling out questionnaires and interviews with mustahik. Testing the data is done with the Validity and Reliability Test, while the hypothesis testing is done with the Paired Statistical t-Test. To measure the effect of sighnificant or not the impact of zakat on the welfare of mustahik, a two-sample paired difference test was conducted using the Wilcoxon signed rank test. The results of research and data analysis, it was found that there was an increase in the average household income before and after zakat assistance with an average income before zakat of Rp. 1,110,000 to Rp. 1,492,241 Likewise with spiritual mustahik. It was found that there was an increase in the score of 10% for each mustahik worship score. Based on the CIBEST Model, the condition of mustahik households after zakat assistance has changed. There was an increase in the prosperous category, the material poor category decreased, the spiritual poor category also decreased while the absolute poor category did not change. The result of the calculated Z value with p value (Asymp sig 2 tailed): 0.000<0.05, indicating that H1 is accepted. Which means that there is a significant or significant difference. This study is expected to show the positive contribution of zakat to the welfare of society.